The Effect of Macroeconomic and Bank-Specific Factors on the Level of Non-Performing Loans in Ghana: Panel Data Regression Analysis - Okine, Abraham Nii Adu; Garr, David Kwashie (Yayasan Ilomata, 2024)
Non-performing loans has posed persistent challenge in Ghana impacting negatively on financial stability and economic growth. Studies have been conducted on NPLs focusing on external factors. However, the real impact of internal determinants has not been explored in the Ghanaian context. This work investigates the effect of macroeconomic and bank-specific variables on NPLs in the Ghana, using existing data from published financial reports of nine firms from 2008 to 2021. This study focuses on NPLs as proxies for the dependent variable, while GDP growth rate, bank’s size, capital adequacy, and unemployment are used as predictor variables. The random effects technique was employed for examination using Ordinary Least Squares. The discoveries prove that GDP has insignificant negative influence on NPLs, whilst bank size and capital adequacy have positive and statistically significant effect on NPLs. Again, unemployment has statistically significant effect on NPLs and bank performance. Banks need to strengthen credit risk management frameworks, particularly for larger institutions, and refine the capital adequacy strategies to align with actual risk exposure. This calls for regulators to adjust capital requirements and explore employment support mechanisms to mitigate the complex relationship between unemployment and NPLs, ensuring that policies are tailored to suit local conditions.